Monomeric ß-amyloid interacts with type-1 insulin-like growth factor receptors to provide energy supply to neurons - Giuffrida, Maria Laura; Tomasello, Marianna F.; Pandini, Giuseppe; Caraci, Filippo; Battaglia, Giuseppe; Busceti, Carla; Di Pietro, Paola; Pappalardo, Giuseppe; Attanasio, Francesco; Chiechio, Santina; Bagnoli, Silvia; Nacmias, Benedetta; et al. (Frontiers in Cellular Neuroscience, 2015)
ß-amyloid (Aß1−42) is produced by proteolytic cleavage of the transmembrane type-1 protein, amyloid precursor protein. Under pathological conditions, Aß1−42self-aggregates into oligomers, which cause synaptic dysfunction and neuronal loss, and are considered the culprit of Alzheimer's disease (AD). However, Aß1−42 is mainly monomeric at physiological concentrations, and the precise role of monomeric Aß1−42 in neuronal function is largely unknown. We report that the monomer of Aß1−42 activates type-1 insulin-like growth factor receptors and enhances glucose uptake in neurons and peripheral cells by promoting the translocation of the Glut3 glucose transporter from the cytosol to the plasma membrane. In neurons, activity-dependent glucose uptake was blunted after blocking endogenous Aß production, and re-established in the presence of cerebrospinal fluid Aß. APP-null neurons failed to enhance depolarization-stimulated glucose uptake unless exogenous monomeric Aß1−42 was added. These data suggest that Aß1−42 monomers were critical for maintaining neuronal glucose homeostasis. Accordingly, exogenous Aß1−42 monomers were able to rescue the low levels of glucose consumption observed in brain slices from AD mutant mice.